Significance of Shodhana Dravyas Used in the Purification of Maharasa, Uprasa, Sadharana Rasa and Dhatu Varga (International Journal of Ayurveda and Pharma Research, 2025)
Rasashastra is the Iatrochemistry of Ayurveda which deals with the various pharmaceutical processes of Shodhana (purification/potentiation), Marana (incineration/calcination), Jarana (polling) and other detailed descriptions of metals, minerals, poisonous plants and animal products which are of therapeutic importance in Ayurveda. A series of pharmaceutical procedures that converts a metal/mineral into a therapeutically effective form is termed as Shodhana. Various methods along with different media are being used for the purification of metals/minerals. Failure to subject certain metals/minerals to the process of Shodhana can have a detrimental impact on the efficacy of the preparations. It is quite interesting to understand the role of media in the purification of Maharasa, Uprasa, Sadharna Rasa and Dhatu Varga.